2017
DOI: 10.1111/crj.12701
|View full text |Cite
|
Sign up to set email alerts
|

Symptom evaluation during the methacholine test: Does it add to the interpretation of the test results based on the PC20FEV1?

Abstract: The occurrence of asthma-like symptoms during the methacholine test was associated with milder airway hyperresponsiveness that would go unnoticed by the PC20FEV1. This finding suggests that SNRs should not be merely classified as having normal responsiveness, as currently recommended, but further assessed for airway inflammation. Our results helped planning a longitudinal study to investigate the prognostic validity of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…They observed greater responsiveness to methacholine expressed as a dose-response slope and a greater proportion of physician-diagnosed asthma in FEV 1 non-responders who were symptomatic compared with the subjects who were asymptomatic. 42 Similar to our data, prominent changes in sR aw and R FOT related to the occurrence of respiratory symptoms during a negative MCT result were recorded by Mansur et al and van Nederveen-Bendien et al 21,43 Furthermore, hyperinflation and gas trapping were previously reported to be associated with cough during MCT. 44 The above observation suggested that respiratory symptoms induced by methacholine in patients who did not meet the diagnostic AHR criteria might be related to smallairways obstruction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They observed greater responsiveness to methacholine expressed as a dose-response slope and a greater proportion of physician-diagnosed asthma in FEV 1 non-responders who were symptomatic compared with the subjects who were asymptomatic. 42 Similar to our data, prominent changes in sR aw and R FOT related to the occurrence of respiratory symptoms during a negative MCT result were recorded by Mansur et al and van Nederveen-Bendien et al 21,43 Furthermore, hyperinflation and gas trapping were previously reported to be associated with cough during MCT. 44 The above observation suggested that respiratory symptoms induced by methacholine in patients who did not meet the diagnostic AHR criteria might be related to smallairways obstruction.…”
Section: Discussionsupporting
confidence: 91%
“…We observed $ 1 respiratory symptom (cough, dyspnea, wheezing, or chest tightness) after inhalation of methacholine in 76.5% of the subjects from the NR group. The issue of methacholine FEV 1 nonresponders who are symptomatic was also addressed by Bohadana et al, 42 who recorded respiratory symptoms in 38.1% of the subjects in whom methacholine did not induced a $ 20% fall in FEV 1. They observed greater responsiveness to methacholine expressed as a dose-response slope and a greater proportion of physician-diagnosed asthma in FEV 1 non-responders who were symptomatic compared with the subjects who were asymptomatic.…”
Section: Discussionmentioning
confidence: 97%
“…All methods were described in detail previously (3). Briefly, the MCT was performed using the 2-minute tidal breathing protocol (1,2).…”
Section: Methodsmentioning
confidence: 99%
“…In a population of adults with suspected asthma, we previously found that 38% (16/42) of methacholine nonresponders experienced asthma-like symptoms during the test (3). Using a continuous measure of responsivenessthe methacholine concentration-response slope (MCRS)we found these so-called "symptomatic non-responders" (SNRs) had increased airway responsiveness below the 20% threshold of fall in FEV1 (3). We hypothesized that this subtle abnormality of responsiveness, which is beyond the reach of the PC20FEV1, might be a risk factor for overt airway hyperresponsiveness (AHR) (and asthma) at a later stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation